Determinants of Corneal Biomechanical Properties in an Adult Chinese Population - Narayanaswamy, Arun; Chung, Ronald S.; Wu, Ren-Yi; Park, Judy; Wong, Wan-Ling; Saw, Seang-Mei; Wong, Tien Y.; Aung, Tin (Ophthalmology (Rochester, Minn.), 2011)
To investigate variations in corneal hysteresis (CH) and corneal resistance factor (CRF) and their ocular and systemic associations in Chinese adults. Population-based, cross-sectional study. We included 1136 subjects of Chinese origin from an ongoing population-based study. All subjects in this population-based study underwent a standardized ocular examination including keratometry (corneal radius of curvature), intraocular pressure (IOP) measurement with Goldmann applanation tonometry, central corneal thickness (CCT), and axial length (AL) assessments. The CH and CRF were measured with the Ocular Response Analyzer. Participants underwent a detailed interview and laboratory investigations that included estimation of nonfasting serum glucose, glycosylated hemoglobin, and lipid profile. We assessed CH, CRF, and their associations with demographic, ocular, and systemic factors. The mean age of study subjects was 55.3±8.4 years and 51.2% were females. The mean CH and CRF were 10.6±1.5 and 10.1±1.6 mmHg, respectively. Women had higher mean CH (10.8 vs 10.4 mmHg; P<0.001) and CRF (10.4 vs. 9.8 mmHg; P<0.001) than men. After adjusting for age, gender, IOP, CCT, keratometry, AL, and diabetes, CH was negatively associated with age (β = −0.034; P<0.001), IOP (β = −0.037; P = 0.01), corneal radius of curvature (β = −0.963; P<0.001), and AL (β = −0.106; P = 0.001); and positively associated with female gender (β = 0.308; P<0.001) and CCT (β = 0.020; P<0.001). The CRF showed a negative association with age (β = −0.023; P<0.001) and corneal radius of curvature (β = −0.771; P<0.001), and was positively associated with female gender (β = 0.368; P<0.001), IOP (β = 0.134; P<0.001) and CCT (β = 0.024; P<0.001). Subjects with diabetes had a higher CH (β = 0.324; P<0.001) and CRF (β = 0.396; P = 0.002) compared with those without diabetes. With advancing age, the CH and CRF in adult Chinese decreased. Women and subjects with diabetes had greater CH and CRF. Corneal biomechanical properties of hysteresis and resistance factor are significantly influenced by IOP, CCT, corneal radius of curvature, and AL. The authors have no proprietary or commercial interest in any of the materials discussed in this article.